Skilled worker migration and trade: Inequality and welfare - Spiros Bougheas; Douglas R. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2010)
We develop a two-sector, two-country model where trade is driven by technological differences. Each country is populated by large number of heterogeneous workers distinguished by their level of skills. Given that one country has a technological advantage in the skilled intensive good when we allow for both trade and migration skilled workers migrate to that country. We analyze the consequences of this migration for both inequality and welfare for the source and the host country.
Keywords: F22; 330; skilled labor; migration; welfare; political economy; Technischer Fortschritt; Entwicklungskonvergenz; Brain Drain; Wohlfahrtseffekt; Mehr-Sektoren-Modell; Zwei-Länder-Modell; Theorie